2006
DOI: 10.1111/j.1083-6101.2002.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Language Choice Online: Globalization and Identity in Egypt

Abstract: The dominance of English on the Internet in the medium's early years caused great consternation about a possible threat to local languages and cultures. Though the hegemony of English online has since weakened, there is still concern about how English and other languages interact online, but there has been almost no research on this issue. This paper combines linguistic analysis, a survey, and interviews to examine English and Arabic language use in online communications by a group of young professionals in Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 12 publications
8
101
0
Order By: Relevance
“…The difference between the use of Dhivehi and English in this domain is much smaller compared to the differences in the friendship and work domains. This might be because some of the respondents feel more comfortable using Dhivehi to express their personal thoughts, similar to the findings of Warschauer, El Said and Zohry (2002). As the family domain would consist of members of different age groups with various levels of English language proficiency, it is not surprising that the use of Dhivehi and English is almost at the same level.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…The difference between the use of Dhivehi and English in this domain is much smaller compared to the differences in the friendship and work domains. This might be because some of the respondents feel more comfortable using Dhivehi to express their personal thoughts, similar to the findings of Warschauer, El Said and Zohry (2002). As the family domain would consist of members of different age groups with various levels of English language proficiency, it is not surprising that the use of Dhivehi and English is almost at the same level.…”
Section: Resultssupporting
confidence: 59%
“…The result on the relationship between proficiency and language choice was similar to studies conducted in face-to-face communication (Rahman et al, 2008;Yeh et al, 2004). Warschauer, El Said and Zohry's (2002) research on the use of English and Arabic in an online context also showed similar results.…”
Section: Relationship Between Language Choice Patterns and Level Of Esupporting
confidence: 59%
See 3 more Smart Citations